Structural design and mechanics research of a bionic pelican floating object fishing device (International Journal of Scientific Research and Management (IJSRM), 2023)
In order to meet the needs of surface floating objects fishing operations in small areas such as lakes and rivers, a fishing device is developed that can be used for high-intensity operations and is highly adaptable to the environment. In this paper, a water and land type bionic pelican surface floating object fishing device is developed based on the MeArm robotic arm combined with a three-degree-of-freedom linkage robotic arm using bionic principles. In order to meet the needs of the fishing function, the overall structure of the surface floating object fishing device was bionically designed by combining the large beak and flexible neck of the pelican, The innovative design of the mouth lower beak opening and closing mechanism, the lower beak gear rack lever slide mechanism, the mouth throat pouch bottom release mechanism and the neck structure are mainly carried out.The structural strength of the device under the most dangerous operating conditions was simulated using finite element analysis software for statics and dynamics simulation. The research results show that the structure of this design is reliable, and the experimental test of the prototype model verifies the validity and reliability of this design scheme, which provides the theoretical and experimental basis for the further development of the subsequent products.